An enhanced distributed control-theoretic time synchronization protocol using sliding mode control for wireless sensor and actuator network - Yeong Chin Koo; Muhammad Nasiruddin Mahyuddin (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Time synchronization is very important in a wireless sensor and actuator network (WSAN) as it provides a common time notation to the WSAN. To handle the time synchronization issue, this paper presented an enhanced distributed control-theoretic time synchronization protocol for wireless sensor and actuator networks, named Time Synchronization using Distributed Observer algorithm with Sliding mode control element (TSDOS). In this protocol, an augmented sliding mode control element is used for robustification purpose.  From the theoretical convergence analysis and simulation results presented in this paper, it proved that the proposed TSDOS is the best if compared to another two algorithms from the literature in terms of cumulative integral absolute error.